STRATEGI INOVATIF PENINGKATAN KESADARAN TENTANG DIABETES MELITUS: MENGURANGI RISIKO MELALUI EDUKASI DAN SCREENING DI MASYARAKAT - Ayudia, Esa Indah; Amatullah, Afifah; Perkasa, Tengku Arief Buana; Asty, Zahra Frizki; Wijayanti, Zilzikridini (Universitas Jambi, 2024)
Diabetes Melitus remains a prominent health challenge globally, particularly in Indonesia, and is therefore included in the country’s disease prevention and control programs. One effective strategy for diabetes Melitus prevention is through community-based education and screening initiatives. This community service activity aimed to provide free facilitation for community members to learn about diabetes Melitus, undergo health checks specifically for random blood glucose levels, then consult with a physician regarding their examination results. The community service activity was conducted at the Letrysa Primary Clinic and began with a pre-test, followed by an educational and counseling session led by an internal medicine specialist. This was then followed by a post-test and screenings of participants' random blood glucose levels and blood pressure. Additionally, participants received free consultations with the internal medicine specialist based on their screening outcomes. The examination results indicated that out of 35 participants, three individuals had abnormal random blood glucose levels. An analysis of pre-test and post-test scores demonstrated that the education and counseling sessions significantly improved participants' understanding and knowledge of diabetes Melitus. Based on these findings, it is recommended that this program be conducted routinely within communities to help prevent Diabetes Melitus.